(3GdEOGQI GdeGdjI (B:s (3eONd GJNGP GdbQGQGJ (B/s - (3Mfaj, YHO GdZaGQs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2002)
(3GdJMdjd GdeGdj hGJNGP GdbQGQGJ,GdJMdjd GdeGdj,GdJNWjW GdeGdj hGdQbGHI,GdGSJKeGQGJ GdQCSeGdjI,GdGJaGb GdQCSeGdj (B-(3eagheg hNUGFUg,CSGdjH Jbjje GdGbJQGMGJ GdGSJKeGQjI aj XQha GdKHGJ hGdJCcO,GdeaGVdI Hjf GdGbJQGMGJ GdGSJKeGQjI aj XQha GdJZjQ h YOe GdJCcO,JcdaI GdCehGd hEJNGP bQGQGJ GdGSJKeGQs
(3HHdjhZQGajG(B:431-436s
Keywords: (3GdGOGQI GdeGdjIs